2019
DOI: 10.1038/s41598-019-50887-6
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative 3D measurements of tibial plateau fractures

Abstract: Fracture gap and step-off measurements on 2DCT-slices probably underestimate the complex multi-directional features of tibial plateau fractures. Our aim was to develop a quantitative 3D-CT (Q3DCT) fracture analysis of these injuries. CT-based 3D models were created for 10 patients with a tibial plateau fracture. Several 3D measures (gap area, articular surface involvement, 3D displacement) were developed and tested. Gaps and step-offs were measured in 2D and 3D. All measurements were repeated by six observers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 23 publications
1
25
0
1
Order By: Relevance
“…Previous studies from our research group showed that 3D fracture quantification may improve outcome prediction of various fracture types. Our results have already shown better agreement on the measures with excellent interobserver agreement (ICC = 0.81), which are comparable with the agreement found in our previous studies (ICC = 0.99 and 0.94) [ 17 , 18 ]. Additionally, the 3D gap area fracture quantification is based on the whole intra-articular aspect of the fracture, rather than one CT-slice.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Previous studies from our research group showed that 3D fracture quantification may improve outcome prediction of various fracture types. Our results have already shown better agreement on the measures with excellent interobserver agreement (ICC = 0.81), which are comparable with the agreement found in our previous studies (ICC = 0.99 and 0.94) [ 17 , 18 ]. Additionally, the 3D gap area fracture quantification is based on the whole intra-articular aspect of the fracture, rather than one CT-slice.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, conventional 2D-CT slices are often insufficient to display the whole extent of complex intra-articular fractures [9][10][11][12][13]. In the last two decades, there is a trend towards fracture classification and analysis based on 3D models [14][15][16][17][18]. Recent studies showed that 3D fracture imaging modalities depict the true extent of the fracture and are less prone to intra-and interobserver variability [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…With these modalities, it is difficult to fully comprehend the true extent of these injuries, since the fracture fragments are often displaced and rotated in multiple directions. 3D visualization and printing modalities have the potential to provide the physician with a better understanding of the fracture pattern and could improve treatment strategy and patient outcome [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therapieplanung stets -nach Durchführung einer entsprechenden Diagnostik, die mindestens aus einer Röntgen-und CT-Bildgebung mit multiplanarer und 3D-Rekonstruktion bestehen sollte [7] -die durchdachte Anwendung einer Frakturklassifikation.…”
Section: Hintergrundunclassified